Radiating Gas Flow Past a Slender Body with an Attached Shock Wave - Singh L.P.; Sharma V.D.; Ram R. (My University, 2025)
A nonlinear problem of a radiating gas flow over a slender body with shock wave attached to its nose is analysed. The behaviour of the shock wave and that of the flow field depends on three important parameters, namely the body thickness ratio, the upstream flow Mach number and the Boltzmann number. Analytical solution of the flow field has been obtained up to second order of the body thickness ratio. The shape of the shock wave attached to the body nose is obtained. The results show how the shock shape is influenced by the ratio of radiative decay length to a typical body length, the Boltzmann number and the upstream flow Mach number.